Interactome disassembly during apoptosis occurs independent of caspase cleavage. Issue 1 (12th January 2017) - Scott, Nichollas E; Rogers, Lindsay D; Prudova, Anna; Brown, Nat F; Fortelny, Nikolaus; Overall, Christopher M; Foster, Leonard J
Abstract: Protein–protein interaction networks (interactomes) define the functionality of all biological systems. In apoptosis, proteolysis by caspases is thought to initiate disassembly of protein complexes and cell death. Here we used a quantitative proteomics approach, protein correlation profiling (PCP), to explore changes in cytoplasmic and mitochondrial interactomes in response to apoptosis initiation as a function of caspase activity. We measured the response to initiation of Fas‐mediated apoptosis in 17, 991 interactions among 2, 779 proteins, comprising the largest dynamic interactome to date. The majority of interactions were unaffected early in apoptosis, but multiple complexes containing known caspase targets were disassembled. Nonetheless, proteome‐wide analysis of proteolytic processing by terminal amine isotopic labeling of substrates (TAILS) revealed little correlation between proteolytic and interactome changes. Our findings show that, in apoptosis, significant interactome alterations occur before and independently of caspase activity. Thus, apoptosis initiation includes a tight program of interactome rearrangement, leading to disassembly of relatively few, select complexes. These early interactome alterations occur independently of cleavage of these protein by caspases. Synopsis: The response of 17, 991 protein interactions to Fas‐mediated apoptosis is monitored using quantitative proteomics (PCP‐SILAC). Initiation of apoptosis leads to dramatic changes in the interactions of caspase targets, independently of caspase cleavage. Quantitative proteomics is used to analyze mitochondrial and cytosolic interactomes in response to apoptosis initiation. The dynamic interactions of 17, 991 interactions among 2, 779 proteins are measured. Interactome alterations occur before and independently of caspase activity. Abstract : The response of 17, 991 protein interactions to Fas‐mediated apoptosis is monitored using quantitative proteomics (PCP‐SILAC). Initiation of apoptosis leads to dramatic changes in the interactions of caspase targets, independently of caspase cleavage.